The role of Kenya in the trans-African spread of maize streak virus strain A - Pande, Daniel; Jäschke, Anja (Virus research, 2017)
Maize streak virus (MSV), the causal agent of maize streak disease (MSD), is the most important viral pathogen of Africa’s staple food crop, maize. Previous phylogeographic analyses have revealed that the most widely-distributed and common MSV variant, MSV-A1, has been repeatedly traversing Africa over the past fifty years with long-range movements departing from either the Lake Victoria region of East Africa, or the region around the convergence of Zimbabwe, South Africa and Mozambique in southern Africa. Despite Kenya being the second most important maize producing country in East Africa, little is known about the Kenyan MSV population and its contribution to the ongoing diversification and trans-continental dissemination of MSV-A1. We therefore undertook a sampling survey in this country between 2008 and 2011, collecting MSD prevalence data in 119 farmers’ fields, symptom severity data for 170 maize plants and complete MSV genome sequence data for 159 MSV isolates. We then used phylogenetic and phylogeographic analyses to show that whereas the Kenyan MSV population is likely primarily derived from the MSV population in neighbouring Uganda, it displays considerably more geographical structure than the Ugandan population. Further, this geographical structure likely confounds apparent associations between virus genotypes and both symptom severity and MSD prevalence in Kenya. Finally, we find that Kenya is probably a sink rather than a source of MSV diversification and movement, and therefore, unlike Uganda, Kenya probably does not play a major role in the trans-continental dissemination of MSV-A1.